Preparation method of dispersing agent for oil well cement
The dispersant for cement for oil wells is prepared by amidation reaction and radical polymerization, and the problems of poor fluidity of cement slurry and conventional polycarboxylic acid dispersants in the prior art are solved, and the problems of long thickening time and low early strength in low temperature cementing are achieved, thereby achieving efficient cement slurry fluidity and rheology performance.
Patent Information
- Application Number
- CN202311246567.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-26
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-09-26
AI Technical Summary
When used in complex environments, the fluidity of existing oil well cement dispersants becomes poor and difficult to pump, and conventional polycarboxylic acid dispersants lead to long thickening time and low early strength in low temperature cementing projects.
The amide-type large monomer was prepared by amidation reaction, and radical polymerization was carried out with the second carboxylic acid monomer and the cationic monomer under the action of the initiator and the chain transfer agent to obtain a dispersant for oil well cement. This method does not require amidation reaction in a solvent environment, and the product is directly used for subsequent polymerization, which is simple, safe and environmentally friendly.
It improves the flow and rheology performance of cement slurry, achieves high dispersion performance and low retarding coexistence, and is suitable for low temperature cementing projects of 40-120℃, solving the problems of long thickening time and low early strength.
Smart Images

Figure CN119708374A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oilfield development cementing operations, and in particular to a method for preparing a dispersant for oil well cement. Background Art
[0002] Cementing is a major step in the oil well construction process. It is a one-time project. The quality of cementing is directly related to subsequent completion, oil production, workover and other operations. Cementing operations mainly include casing installation and cementing. Cementing is to pump cement slurry into the annulus between the casing and the wellbore, and the pumped cement slurry is required to have good flow properties. However, with the deepening of exploration and development, there are more and more complex environments. In actual construction, it is necessary to add a variety of retarders, fluid loss agents, weighting agents, latex materials and other admixtures or additives to the cement slurry, which often leads to poor fluidity of the slurry and difficulty in pumping. Therefore, it is often necessary to add dispersants to the cement slurry to improve the flow properties of the cement slurry and improve its rheological properties, so that the cement slurry can achieve turbulent displacement at low pump pressure and improve the quality of cementing in oil and gas wells.
[0003] At present, the most widely used oil well cement dispersant in the world is sulfonated acetone-formaldehyde condensate dispersant. The product color is usually reddish brown powder. The dispersion mechanism is to adsorb on the surface of cement particles, increase the Zeta potential of cement particles, and disperse through electrostatic repulsion. It has good temperature and salt resistance. However, as people's awareness of green, safety and environmental protection gradually increases, the production and use of sulfonated acetone-formaldehyde condensate dispersants are also restricted. The reasons are as follows: First, its production raw materials acetone and formaldehyde are toxic and polluting, resulting in environmentally unfriendly production and application links; secondly, sulfonated acetone-formaldehyde has a single structure and is limited by its dispersion mechanism. The dosage is large when used and the dispersion efficiency is low; finally, oil well cement admixtures are constantly being innovated, and there is a problem of incompatibility with new additives.
[0004] Polycarboxylate (PCE) is a comb-shaped polymer composed of anionic anchoring group main chain and hydrophilic nonionic long branched chain. It is a new generation of pollution-free cement dispersant with excellent performance. In 1981, Japan invented the first generation of polycarboxylate (PCE) (JP57118058). Due to its good molecular design, it can meet different application environments. After more than 20 years of development, it has completely occupied the world market of building concrete water reducers and is known as high-performance water reducers in China. However, the study of Zhai et al. "Characteristics of polycarboxylate-based dispersant suitable for medium and low temperature oil well cementing" shows that conventional polycarboxylate water reducers can not fully meet the needs of cementing when directly applied to oil well cement. The carboxylic acid group of the main chain of conventional polycarboxylic acid molecules can be adsorbed on the positively charged aluminate phase surface, and can also be adsorbed on the negatively charged silicate phase surface through the bridge of calcium ions, and the dispersion effect is achieved through electrostatic repulsion and steric hindrance. However, the high acid-ether ratio, high charge density and strong adsorption performance in its molecular structure will delay the formation and growth of CSH nuclei and hinder the cement hydration process, especially in low-temperature cementing projects at 40-120°C, showing problems such as long thickening time and low early strength. In addition, when conventional polycarboxylic acid dispersants are used together with anionic fluid loss reducers and retarders commonly used in oil well cement, there is competitive adsorption, poor dispersion effect, and possible compatibility problems. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing a dispersant for oil well cement to solve the above problems.
[0006] To achieve the above object, the present invention provides a method for preparing a dispersant for oil well cement, the method comprising:
[0007] The first carboxylic acid monomer, a catalyst and a polymerization inhibitor are added to the monoamine-terminated polyether to obtain an amide-type macromonomer through an amidation reaction;
[0008] The amide type macromonomer, the second carboxylic acid monomer and the cationic monomer undergo free radical polymerization reaction under the action of an initiator and a chain transfer agent to obtain the dispersant for oil well cement.
[0009] Optionally, the first carboxylic acid monomer, the catalyst and the polymerization inhibitor are added to the monoamine-terminated polyether to obtain an amide-type macromonomer through an amidation reaction, including:
[0010] Under nitrogen protection, the monoamine-terminated polyether is heated to 55° C. to 70° C., and then the first carboxylic acid monomer, the catalyst and the inhibitor are added;
[0011] The temperature is then continued to rise to 130-170° C. and maintained at a constant temperature for 5-8 hours to carry out an amidation reaction to obtain an amide-type macromonomer.
[0012] Optionally, the general formula of the monoamine-terminated polyether is:
[0013]
[0014] Here, x and y are the average added mole numbers of polypropylene glycol (PPO) and polyethylene glycol (PEO), respectively, and x+y is an integer of 20 to 60.
[0015] Optionally, the molar ratio of the monoamine-terminated polyether to the first carboxylic acid monomer is 1:1.05 to 1.10.
[0016] Optionally, the first carboxylic acid monomer includes at least one of the following: maleic anhydride, acrylic acid, maleic acid, and methacrylic acid.
[0017] Optionally, the catalyst includes at least one of the following: p-toluenesulfonic acid, concentrated sulfuric acid, ethylsulfonic acid, benzenesulfonic acid; wherein the mass of the catalyst is 0.5% to 5% of the mass of the monoamine-terminated polyether.
[0018] Optionally, the polymerization inhibitor includes at least one of the following: hydroquinone, p-tert-butylcatechol, 2,6-di-tert-butyl-p-methylphenol, and p-benzoquinone; wherein the mass of the polymerization inhibitor is 0.1% to 2% of the mass of the first carboxylic acid monomer.
[0019] Optionally, the amide macromonomer, the second carboxylic acid monomer and the cationic monomer undergo free radical polymerization under the action of an initiator and a chain transfer agent to obtain the dispersant for oil well cement, including:
[0020] Adding a mixed solution of the amide macromonomer and the cationic monomer into a reaction container as a base solution;
[0021] Adding the mixed solution of the second carboxylic acid monomer and the chain transfer agent and the initiator into the reaction container in a dropwise manner to carry out a free radical polymerization reaction;
[0022] After the free radical polymerization reaction, an alkaline substance is added to the product to obtain a dispersant.
[0023] Optionally, the molar ratio of the amide macromonomer to the molar sum of the second carboxylic acid monomer and the cationic monomer is 1:2 to 1:5; the molar ratio of the cationic monomer to the molar sum of the second carboxylic acid monomer and the cationic monomer is 1:1 to 1:5.
[0024] Optionally, the first carboxylic acid monomer and the second carboxylic acid monomer are the same.
[0025] Optionally, the cationic monomer includes at least one of the following: methacryloyloxyethyltrimethylammonium chloride, dimethyldiallylammonium chloride, methacrylamidepropyltrimethylammonium chloride, and allyltrimethylammonium chloride.
[0026] Optionally, the initiator includes at least one of the following: ammonium persulfate, sodium persulfate, potassium persulfate; wherein the mass of the initiator is 0.5% to 4% of the total mass of the amide macromonomer, the second carboxylic acid monomer and the cationic monomer.
[0027] Optionally, the chain transfer agent includes at least one of the following: sodium hypophosphite, sodium methyl methacrylate sulfonate, thioglycolic acid, 3-mercaptopropionic acid, and mercaptoethanol; wherein the mass of the chain transfer agent is 0.2% to 3% of the total mass of the amide macromonomer, the second carboxylic acid monomer, and the cationic monomer.
[0028] Optionally, the dripping time of the mixed solution of the second carboxylic acid monomer and the chain transfer agent is 2 to 4 hours, and the dripping time of the initiator is 2.5 to 4.5 hours; wherein the dripping time of the initiator is greater than the dripping time of the mixed solution of the second carboxylic acid monomer and the chain transfer agent.
[0029] Optionally, the conditions of the free radical polymerization reaction include: a reaction temperature of 60 to 90° C. and a total polymerization reaction time of 4 to 8 hours.
[0030] Optionally, the alkaline substance includes at least one of the following: sodium hydroxide, potassium hydroxide, calcium hydroxide, sodium carbonate; wherein the alkaline substance adjusts the pH value of the product to 6-8.
[0031] Technical effects and advantages of the present invention:
[0032] The invention provides a method for preparing a dispersant for oil well cement, the method comprising: adding a first carboxylic acid monomer, a catalyst and a polymerization inhibitor into a monoamine-terminated polyether to obtain an amide-type macromonomer through an amidation reaction; and subjecting the amide-type macromonomer, a second carboxylic acid monomer and a cationic monomer to a free radical polymerization reaction under the action of an initiator and a chain transfer agent to obtain the dispersant for oil well cement.
[0033] The preparation of the unsaturated amide macromonomer in the present invention can be subjected to an amidation reaction without the need for a solvent environment, and the product can be directly used for subsequent polymerization reactions without further treatment, and the production process is simple, the process is safe and environmentally friendly, and the atomic conversion rate is high. Moreover, the anion and cation adsorption anchoring effects in the dispersant molecular structure are complementary, and the proportion of carboxylic acid in the polycarboxylic acid molecular structure can be reduced while maintaining the original adsorption and dispersion effect, and the steric hindrance of the long side chain of the block polyether can effectively prevent cement particles from agglomerating, improve the rheology of cement slurry, and achieve high dispersibility and low retarding coexistence.
[0034] Other features and advantages of the present invention will be described in the following description, and partly become obvious from the description, or be understood by implementing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 The present invention is a flow chart of a method for preparing a dispersant for oil well cement;
[0036] Figure 2 This is the infrared spectrum of amide type polycarboxylic acid dispersant for oil well cement;
[0037] Figure 3 This is the thermogravimetric curve of the amide type polycarboxylic acid dispersant for oil well cement;
[0038] Figure 4 is the thickening curve of 0.5% sulfonated aldehyde ketone polycondensate (a) (85°C×46.2MPa);
[0039] Figure 5 The thickening curve (85°C×46.2MPa) of the amide type polycarboxylic acid dispersant (b) for oil well cement prepared in Example 1 at 0.5%. DETAILED DESCRIPTION
[0040] The technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings provided by the present invention, and the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] It should be noted that the structures, proportions, sizes, etc. illustrated in the drawings of this specification are only used to match the contents disclosed in the specification for people familiar with this technology to understand and read, and are not used to limit the limiting conditions for the implementation of the present invention, so they have no substantial technical significance. Any modification of the structure, change of the proportion relationship or adjustment of the size should still fall within the scope of the technical content disclosed by the present invention without affecting the effects and purposes that can be achieved by the present invention. At the same time, the terms such as "upper", "lower", "left", "right", "middle" and "one" quoted in this specification are only for the convenience of description, and are not used to limit the scope of the implementation of the present invention. The change or adjustment of their relative relationship should also be regarded as the scope of the implementation of the present invention without substantially changing the technical content.
[0042] The present invention discloses a method for preparing a dispersant for oil well cement. Figure 1 For detailed explanation:
[0043] 1. Preparation of unsaturated amide macromonomer: adding a first carboxylic acid monomer, a catalyst and a polymerization inhibitor to a monoamine-terminated polyether to obtain an amide macromonomer through an amidation reaction.
[0044] Specifically, under nitrogen protection, the monoamine-terminated polyether is heated to 55°C-70°C, the first carboxylic acid monomer, catalyst and inhibitor are added, and then the temperature is slowly raised to 130-170°C, and the constant temperature is maintained for 5-8 hours for full amidation, and the temperature is lowered to obtain an amide-type macromonomer.
[0045] Wherein, the molar ratio of the monoamine-terminated polyether to the first carboxylic acid monomer is 1:1.05-1.10.
[0046] Wherein, the general formula (I) of the monoamine-terminated polyether is:
[0047]
[0048] In the formula, x and y are the average added mole numbers of polypropylene glycol (PPO) and polyethylene glycol (PEO), respectively, x+y is an integer of 20 to 60, x is preferably an integer of 0 to 10, and y is preferably an integer of 20 to 50.
[0049] Wherein, the first carboxylic acid monomer is one or a combination of two or more of maleic anhydride, acrylic acid, maleic acid and methacrylic acid in any proportion.
[0050] The catalyst is one or a combination of two or more of p-toluenesulfonic acid, concentrated sulfuric acid, ethylsulfonic acid and benzenesulfonic acid in any proportion, and its usage is 0.5% to 5% of the mass of the monoamine-terminated polyether, preferably 2% to 3%.
[0051] The polymerization inhibitor is one or two of hydroquinone, p-tert-butylcatechol, 2,6-di-tert-butyl-p-methylphenol, and p-benzoquinone in any proportion, and its dosage is 0.1% to 2% of the mass of the carboxylic acid monomer, preferably 0.5% to 1%.
[0052] 2. Free radical polymerization reaction: The amide macromonomer, the second carboxylic acid monomer and the cationic monomer undergo free radical polymerization reaction under the action of an initiator and a chain transfer agent to obtain the dispersant for oil well cement.
[0053] Specifically, a mixed solution of unsaturated amide macromonomer and cationic monomer is added to the reaction container as a base liquid before the reaction starts; a mixed solution of the second carboxylic acid monomer and chain transfer agent, and an initiator solution are added dropwise to the reaction container for reaction, thereby improving the macromonomer conversion rate.
[0054] During the entire reaction process, the solid content is controlled at 30-55wt%, the reaction temperature is controlled at 60-90°C, the dripping time of the mixed solution of the second carboxylic acid monomer and the chain transfer agent and the initiator solution are 2-4h and 2.5-4.5h respectively, and the dripping time of the initiator solution must be greater than the dripping time of the mixed solution of the second carboxylic acid monomer and the chain transfer agent. After the initiator solution is completed, it continues to be heat-insulated and aged for 0.5-2h, and the total polymerization reaction time is controlled at 4h-8h.
[0055] After the polymerization reaction is completed, the mixture is cooled to room temperature, and one or more of sodium hydroxide, potassium hydroxide, calcium hydroxide and sodium carbonate are added to the reaction product to adjust the pH value to 6-8.
[0056] The molar ratio of the various monomers satisfies: unsaturated amide macromonomer: (second carboxylic acid monomer + cationic monomer) = 1:2 to 1:5, cationic monomer: (second carboxylic acid monomer + cationic monomer) = 1:1 to 1:5.
[0057] Wherein, the second carboxylic acid monomer is the same as the first carboxylic acid monomer.
[0058] The cationic monomer is one or a combination of any two or more of methacryloyloxyethyl trimethyl ammonium chloride, dimethyl diallyl ammonium chloride, methacrylamide propyl trimethyl ammonium chloride and allyl trimethyl ammonium chloride.
[0059] The initiator is one or more of ammonium persulfate, sodium persulfate and potassium persulfate, and its usage is 0.5% to 4% of the total mass of the unsaturated amide macromonomer, the second carboxylic acid monomer and the cationic monomer, preferably 1.5% to 3%.
[0060] The chain transfer agent is one or more of sodium hypophosphite, sodium methyl propylene sulfonate, thioglycolic acid, 3-mercaptopropionic acid, and mercaptoethanol, and the amount used is 0.2% to 3% of the total mass of the unsaturated amide macromonomer, the second carboxylic acid monomer, and the cationic monomer, preferably 0.5% to 1.5%.
[0061] In order to better explain the present solution, specific embodiments are provided below.
[0062] Example 1
[0063] A method for preparing an amide type polycarboxylic acid dispersant for oil well cement comprises the following steps:
[0064] (1) 2000 parts by weight of a monoamine-terminated polyether (x=10, y=31) with a weight average molecular weight of 2000 was placed in a reaction vessel, nitrogen was introduced for protection, and the reaction vessel was stirred and heated to 70° C. 107.8 parts of maleic anhydride, 100 parts of p-toluenesulfonic acid and 2.2 parts of hydroquinone were added in sequence, and the temperature was continued to rise to 170° C. The temperature was kept constant for 6 hours and then cooled to room temperature to obtain an unsaturated amide macromonomer;
[0065] (2) In parts by weight, 2100 parts of the unsaturated amide macromonomer in (1) and 864 parts of methacryloyloxyethyl trimethyl ammonium chloride are weighed and dissolved in 3000 parts of water and placed in a reaction container to form a base liquid, 180 parts of acrylic acid and 84 parts of sodium hypophosphite are dissolved in 1000 parts of water to form a liquid A, and 112 parts of ammonium persulfate are dissolved in 700 parts of water to form a liquid B for standby use. Nitrogen is introduced into the reaction container for protection, and the reaction container is stirred and heated to 70° C. Liquid A and liquid B are added to the reaction container in a dropwise manner for 3 hours and 3.5 hours, respectively. After the dropwise addition is completed, the temperature is maintained for aging for 1 hour, and the mixture is cooled to room temperature. The pH value is adjusted to 8 with sodium hydroxide to obtain an amide polycarboxylic acid dispersant for oil well cement.
[0066] Example 2
[0067] A method for preparing an amide type polycarboxylic acid dispersant for oil well cement comprises the following steps:
[0068] (1) 2000 parts by weight of a monoamine-terminated polyether (x=10, y=31) with a weight average molecular weight of 2000 was placed in a reaction vessel, nitrogen was introduced for protection, the reaction vessel was stirred and heated to 55° C., 90 parts of methacrylic acid, 10 parts of p-toluenesulfonic acid and 0.1 parts of hydroquinone were added in sequence, the temperature was continued to rise to 130° C., the temperature was kept constant for 8 hours and then cooled to room temperature to obtain an unsaturated amide macromonomer;
[0069] (2) In parts by weight, 2090 parts of the unsaturated amide macromonomer in (1) and 269 parts of dimethyldiallylammonium chloride were weighed and dissolved in 2500 parts of water and placed in a reaction container to form a base liquid, 86 parts of methacrylic acid and 4.7 parts of thioglycolic acid were dissolved in 500 parts of water to form a liquid A, and 11.7 parts of potassium persulfate were dissolved in 500 parts of water to form a liquid B for standby use. Nitrogen was introduced into the reaction container for protection, and the reaction container was stirred and heated to 65° C. Liquid A and liquid B were added dropwise to the reaction container for 4 hours and 4.5 hours, respectively. After the dropwise addition was completed, the temperature was kept for aging for 0.5 hours, and the mixture was cooled to room temperature. The pH was adjusted to 6 with sodium hydroxide to obtain an amide polycarboxylic acid dispersant for oil well cement.
[0070] Example 3
[0071] A method for preparing an amide type polycarboxylic acid dispersant for oil well cement comprises the following steps:
[0072] (1) In parts by weight, 1000 parts of a monoamine-terminated polyether (x=3, y=19) having a weight average molecular weight of 1000 is placed in a reaction vessel, nitrogen is introduced for protection, the reaction vessel is stirred and heated to 65° C., 108 parts of maleic anhydride, 20 parts of p-toluenesulfonic acid and 1.1 parts of hydroquinone are added in sequence, the temperature is continuously raised to 150° C., the temperature is kept constant for 5 hours and then lowered to room temperature to obtain an unsaturated amide macromonomer;
[0073] (2) In parts by weight, 1100 parts of the unsaturated amide type macromonomer in (1) and 692 parts of methacryloyloxyethyl trimethyl ammonium chloride are weighed and dissolved in 1500 parts of water and placed in a reaction container to form a base liquid, 216 parts of acrylic acid and 17 parts of sodium hypophosphite are dissolved in 600 parts of water to form a liquid A, and 52 parts of ammonium persulfate are dissolved in 500 parts of water to form a liquid B for standby use. Nitrogen is introduced into the reaction container for protection, and the reaction container is stirred and heated to 75° C. Liquid A and liquid B are added to the reaction container in a dropwise manner, with the dropwise addition time being 3 h and 3.5 h respectively. After the dropwise addition is completed, the temperature is maintained for aging for 0.5 h, and the mixture is cooled to room temperature. The pH value is adjusted to 7 with sodium hydroxide to obtain an amide type polycarboxylic acid dispersant for oil well cement.
[0074] Example 4
[0075] A method for preparing an amide type polycarboxylic acid dispersant for oil well cement comprises the following steps:
[0076] (1) In parts by weight, 1000 parts of a monoamine-terminated polyether (x=3, y=19) with a weight average molecular weight of 1000 is placed in a reaction container, nitrogen is introduced for protection, and the reaction is stirred and heated to 60° C. Then, 79 parts of acrylic acid, 30 parts of p-toluenesulfonic acid and 0.8 parts of hydroquinone are added, and the temperature is continuously raised to 135° C. The temperature is kept constant for 7 hours and then lowered to room temperature to obtain an unsaturated amide macromonomer;
[0077] (2) In parts by weight, 1080 parts of the unsaturated amide macromonomer in (1) and 538 parts of dimethyldiallyl ammonium chloride were weighed and dissolved in 1300 parts of water and placed in a reaction container to form a base liquid, 144 parts of acrylic acid and 15 parts of mercaptoethanol were dissolved in 500 parts of water to form a liquid A, and 31 parts of sodium persulfate were dissolved in 500 parts of water to form a liquid B for standby use. Nitrogen was introduced into the reaction container for protection, and the reaction container was stirred and heated to 70° C. Liquid A and liquid B were added to the reaction container in a dropwise manner for 2 hours and 2.5 hours, respectively. After the dropwise addition was completed, the temperature was maintained for 1 hour, and the mixture was cooled to room temperature. The pH was adjusted to 7 with sodium hydroxide to obtain an amide polycarboxylic acid dispersant for oil well cement.
[0078] The above dispersants were tested and analyzed, and the results are as follows:
[0079] Figure 2 This is the infrared spectrum of the amide type polycarboxylic acid dispersant for oil well cement prepared in Example 1. As can be seen from the figure, 1565cm-1 and 1110cm -1 The stretching vibration peaks at 1725 cm-1 are the amide bond -CONH- on the side chain of the amide macromonomer and the -COC- on the block polyether. -1 The stretching vibration peak of the carboxyl group -COOH on acrylic acid is 2872 cm -1 1565cm -1 and (4) (5) (6) (7) (8) (9) (11) (12) (13) (14) (15) (16) (17) (18) (19) (20) (21) (22) (23) (24) (25) (26) (27) (28) (29) (29) (30) (41) (42) (43) (44) (55) (45) (46) (47) (48) (49) (50) (51) (52) (53) (54) (55) (56) (57) (58) (59) (60) (61) (62) (64) (71) (65) (72) (66) (73) (84) (95) (96) (97) (98) (101) (111) (112) (
[0080] Figure 3 This is a thermogravimetric analysis diagram of the amide type polycarboxylic acid dispersant for oil well cement prepared in Example 1. It can be seen from the figure that the polymer starts to decompose at 216°C, and the main decomposition is divided into two steps, corresponding to the decomposition of the long side chain of the polyether and the decomposition of the main chain of the molecule, that is, the polymer can be used in a thermal environment below 216°C and meet the requirements of 40-120°C cementing construction.
[0081] The preparation of oil well cement slurry and the test method of dispersant performance were tested with reference to GB / T 19139-2012 "Test Methods for Oil Well Cement" and SYT 5504.3-2018 "Evaluation Methods for Oil Well Cement Admixtures Part 3: Drag Reducers". Sulfonated aldehyde ketone polycondensate was used as comparative example 1, and the rheological properties, thickening time, and compressive strength of the examples and comparative examples were evaluated. The evaluation results are shown in Table 1.
[0082] Table 1 Evaluation results of different dispersants performance
[0083]
[0084] Note: Oil well cement slurry formula: Jiahua G grade oil well cement + 0.5% bwoc dispersant, water-solid ratio 0.44; where % bwoc is expressed as the mass percentage of cement.
[0085] According to Table 1, the ratio of thickening time and the ratio of compressive strength are compared with the cement paste. Under the thickening test conditions of set temperature 85°C, set pressure 46.2MPa, and heating time 40min, the thickening time of the cement paste is 68min; the addition of dispersant will lead to different degrees of extension of thickening time, among which the sulfonated aldehyde ketone condensation polymer has the shortest extension time, and its thickening time is 83min, which is 1.19 times that of the neat paste; the amide type polycarboxylic acid dispersant for oil well cement of the present invention shows a slightly longer thickening time than the sulfonated aldehyde ketone condensation polymer, between 1.41 and 1.73 times, but both meet the technical indicators in the petroleum and natural gas industry standard SY / T 5504.3-2018, which is not more than 2 times; the 24h compressive strength of the amide type polycarboxylic acid dispersant for oil well cement of the present invention is slightly lower than that of the sulfonated aldehyde ketone condensation polymer, and both meet the requirements of the SY / T5504.3-2018 index, and no strong retarding and low early strength occur.
[0086] From the rheological properties and Figure 4 and Figure 5 It can be seen from the medium thickening curve that under the same dosage, the dispersion efficiency of the amide type polycarboxylic acid dispersant for oil well cement of the present invention is much higher than that of the sulfonated aldehyde ketone condensation polymer, and it has better rheological properties and lower initial consistency. In addition, the thickening line is stable, no bulging or stepping occurs, and it thickens almost at a "right angle".
[0087] After cement is hydrated with water, the surface of the silicate phase is negatively charged, and the surface of the aluminate phase is positively charged. The interaction between the positive and negative charges causes the cement slurry to flocculate, the viscosity increases, and the construction pumping pressure increases; the dispersant is mainly adsorbed on the positive potential point of the cement particles through the anionic group, changes the surface electrical properties of the cement particles and forms a hydration film of a certain thickness to disperse the cement flocculated particles and reduce the viscosity; the sulfonated aldehyde ketone polycondensate is a linear polymer and contains only sulfonic acid adsorption groups, so its action mechanism is only electrostatic repulsion to disperse the cement particles, and the dispersion efficiency is not high; the main chain of the amide type polycarboxylic acid dispersant for oil well cement of the present invention has both carboxyl and cationic adsorption groups, the long side chains of the block polyether are connected by amide bonds, the long side chains have steric hindrance and can form a hydration film, and the dispersion efficiency is greatly improved.
[0088] The present invention also provides a device for preparing a dispersant for oil well cement, the device comprising: a reaction unit, used for adding a first carboxylic acid monomer, a catalyst and an inhibitor to a monoamine-terminated polyether to obtain an amide-type macromonomer through an amidation reaction; and an obtaining unit, used for subjecting the amide-type macromonomer, a second carboxylic acid monomer and a cationic monomer to a free radical polymerization reaction under the action of an initiator and a chain transfer agent to obtain the dispersant for oil well cement.
[0089] Since the content protected by this device is similar to that protected by the above method, no further introduction will be given here. Please refer to the discussion section of the above method for details.
[0090] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a dispersant for oil well cement, characterized in that: The method comprises: The first carboxylic acid monomer, a catalyst and a polymerization inhibitor are added to the monoamine-terminated polyether to obtain an amide-type macromonomer through an amidation reaction; The amide type macromonomer, the second carboxylic acid monomer and the cationic monomer undergo free radical polymerization reaction under the action of an initiator and a chain transfer agent to obtain the dispersant for oil well cement.
2. The method according to claim 1, characterized in that The first carboxylic acid monomer, the catalyst and the polymerization inhibitor are added to the monoamine-terminated polyether to obtain an amide-type macromonomer through an amidation reaction, including: Under nitrogen protection, the monoamine-terminated polyether is heated to 55° C. to 70° C., and then the first carboxylic acid monomer, the catalyst and the inhibitor are added; The temperature is then continued to rise to 130-170° C. and maintained at a constant temperature for 5-8 hours to carry out an amidation reaction to obtain an amide-type macromonomer.
3. The method according to claim 1, characterized in that The general formula of the monoamine-terminated polyether is: Here, x and y are the average added mole numbers of polypropylene glycol (PPO) and polyethylene glycol (PEO), respectively, and x+y is an integer of 20 to 60.
4. The method according to claim 1, characterized in that: The molar ratio of the monoamine-terminated polyether to the first carboxylic acid monomer is 1:1.05-1.
10.
5. The method according to claim 1, characterized in that The first carboxylic acid monomer comprises at least one of the following: maleic anhydride, acrylic acid, maleic acid, and methacrylic acid.
6. The method according to claim 1, characterized in that The catalyst comprises at least one of the following: p-toluenesulfonic acid, concentrated sulfuric acid, ethylsulfonic acid, benzenesulfonic acid; wherein the mass of the catalyst is 0.5% to 5% of the mass of the monoamine-terminated polyether.
7. The method according to claim 1, characterized in that The polymerization inhibitor comprises at least one of the following: hydroquinone, p-tert-butylcatechol, 2,6-di-tert-butyl-p-methylphenol, and p-benzoquinone; wherein the mass of the polymerization inhibitor is 0.1% to 2% of the mass of the first carboxylic acid monomer.
8. The method according to claim 1, characterized in that The amide type macromonomer, the second carboxylic acid monomer and the cationic monomer undergo free radical polymerization under the action of an initiator and a chain transfer agent to obtain the dispersant for oil well cement, including: Adding a mixed solution of the amide macromonomer and the cationic monomer into a reaction container as a base solution; Adding the mixed solution of the second carboxylic acid monomer and the chain transfer agent and the initiator into the reaction container in a dropwise manner to carry out a free radical polymerization reaction; After the free radical polymerization reaction, an alkaline substance is added to the product to obtain a dispersant.
9. The method according to claim 1, characterized in that: The molar ratio of the amide macromonomer to the molar sum of the second carboxylic acid monomer and the cationic monomer is 1:2 to 1:5; the molar ratio of the cationic monomer to the molar sum of the second carboxylic acid monomer and the cationic monomer is 1:1 to 1:
5.
10. The method according to claim 1, characterized in that The first carboxylic acid monomer and the second carboxylic acid monomer are the same.
11. The method according to claim 1, characterized in that: The cationic monomer includes at least one of the following: methacryloyloxyethyl trimethyl ammonium chloride, dimethyl diallyl ammonium chloride, methacrylamide propyl trimethyl ammonium chloride, and allyl trimethyl ammonium chloride.
12. The method according to claim 1, characterized in that The initiator comprises at least one of the following: ammonium persulfate, sodium persulfate, potassium persulfate; wherein the mass of the initiator is 0.5% to 4% of the total mass of the amide macromonomer, the second carboxylic acid monomer and the cationic monomer.
13. The method according to claim 1, characterized in that The chain transfer agent comprises at least one of the following: sodium hypophosphite, sodium methyl methacrylate sulfonate, thioglycolic acid, 3-mercaptopropionic acid, and mercaptoethanol; wherein the mass of the chain transfer agent is 0.2% to 3% of the total mass of the amide macromonomer, the second carboxylic acid monomer, and the cationic monomer.
14. The method according to claim 8, characterized in that The dripping time of the mixed solution of the second carboxylic acid monomer and the chain transfer agent is 2 to 4 hours, and the dripping time of the initiator is 2.5 to 4.5 hours; wherein the dripping time of the initiator is greater than the dripping time of the mixed solution of the second carboxylic acid monomer and the chain transfer agent.
15. The method according to claim 8, characterized in that The conditions of the free radical polymerization reaction include: a reaction temperature of 60 to 90° C. and a total polymerization reaction time of 4 to 8 hours.
16. The method according to claim 8, characterized in that The alkaline substance includes at least one of the following: sodium hydroxide, potassium hydroxide, calcium hydroxide, and sodium carbonate; wherein the alkaline substance adjusts the pH value of the product to 6-8.
Citation Information
Patent Citations
Cement dispersant
JP1982118058A
Method for synthesizing polycarboxylic acid high-property water reducer by copolymerization of amidated active monomers
CN102181020A
Polyether-amide type polycarboxylic high-efficiency water reducer and preparation method thereof
CN104031216A
Amphiprotic polycarboxylic acid dispersant for oil well cement as well as preparation method and application
CN108997536A